Imagined histories : American historians interpret the past - Molho, Anthony; Wood, Gordon S. (Book collections on Project MUSE., 1998)
This collection of essays by twenty-one distinguished American historians reflects on a peculiarly American way of imagining the past. At a time when history-writing has changed dramatically, the authors discuss the birth and evolution of historiography in this country, from its origins in the late nineteenth century through its present, more cosmopolitan character." " In the book's first part, concerning recent historiography, are chapters on exceptionalism, gender, economic history, social theory, race, and immigration and multiculturalism. Authors are Daniel Rodgers, Linda Kerber, Naomi Lamoreaux, Dorothy Ross, Thomas Holt, and Philip Gleason. The three American centuries are discussed in the second part, with chapters by Gordon Wood, George Fredrickson, and James Patterson. The third part is a chronological survey of non-American histories, including that of Western civilization, ancient history, the middle ages, early modern and modern Europe, Russia, and Asia. Contributors are Eugen Weber, Richard Saller, Gabrielle Spiegel, Anthony Molho, Philip Benedict, Richard Kagan, Keith Baker, Joseph Zizak, Volker Berghahn, Charles Maier, Martin Malia, and Carol Gluck." "Together, these scholars reveal the unique perspective American historians have brought to the past of their own nation as well as that of the world. Formerly writing from a conviction that America had a singular destiny, American historians have gradually come to share viewpoints of historians in other countries about which they write. The result is the virtual disappearance of what was a distinctive American voice. That voice is the subject of this book.